El Impuesto de Alcabala en el Perú - Durán Rojo, Luis Alberto (2014)
The present paper is a thorough study on the recent developments of excise tax in Peru. It begins by showing the most recent regulatory treatment on this tax, then focusing on the current system of it, analyzing the most relevant aspects of the excise tax, aiming to be a contribution to the future improvement of this tax.